Dynamic response analysis for multi-degrees-of-freedom parallel mechanisms with various types of three-dimensional clearance joints. (28th May 2021) - Yonghao, Jia; Xiulong, Chen
For spatial multibody systems, the dynamic equations of multibody systems with compound clearance joints have a high level of nonlinearity. The coupling between different types of clearance joints may lead to abundant dynamic behavior. At present, the dynamic response analysis of the spatial parallel mechanism considering the three-dimensional (3D) compound clearance joint has not been reported. This work proposes a modeling method to investigate the influence of the 3D compound clearance joint on the dynamics characteristics of the spatial parallel mechanism. For this purpose, 3D kinematic models of spherical clearance joint and revolute joint with radial and axial clearances are derived. Contact force is described as normal contact and tangential friction and later introduced into the nonlinear dynamics model, which is established by the Lagrange multiplier technique and Jacobian of constraint matrix. The influences of compound clearance joint and initial misalignment of bearing axes on the system are analyzed. Furthermore, validation of dynamics model is evaluated by ADAMS and Newton–Euler method. This work provides an essential theoretical basis for studying the influences of 3D clearance joints on dynamic responses and nonlinear behavior of parallel mechanisms.